Inflammatory storm and metabolic disorders: unraveling heterogeneity in mortality risk for comorbid diabetes mellitus and heart failure via the C-reactive protein-triglyceride-glucose index - Zhang, Na; Xie, Lin; Zhang, Shuhua; Wang, Qun; Lu, Hengcheng; Xiong, Zhiyu; Xie, Guobo; Sheng, Guotai; Yang, Hongyi; He, Shiming; Liao, Tanghong; Wang, Wei; et al. (Frontiers in Endocrinology, 2025)
IntroductionAcute decompensated heart failure (ADHF), a critical cardiovascular emergency, is driven by a metabolic and inflammatory imbalance that serves as the central mechanism of disease progression. This study aims to analyze the heterogeneity of mortality risk in patients with comorbid diabetes mellitus (DM) and HF using the C-reactive protein-triglyceride-glucose index (CTI).MethodsThis study evaluated 1,051 ADHF patients from the Jiangxi-ADHF II cohort. The Boruta algorithm, a fully automated feature selection method, was applied to identify key predictive variables and rank their importance. Cox proportional hazard models were constructed to assess the association between the CTI and 30-day mortality risk in ADHF patients, stratified by DM status. To further elucidate the nonlinear characteristics of risk associations, restricted cubic splines were employed to construct dose-response relationship curves. Additionally, heatmaps were used to assess the joint association of CTI components with mortality risk.ResultsThe 30-day follow-up revealed a mortality rate of 8.3%. Through the Boruta algorithm and multivariate Cox regression analysis, we identified CTI as a key prognostic factor for short-term mortality risk in ADHF patients, especially in those with comorbid DM. The restricted cubic splines model further confirmed the linear and non-linear associations between CTI and mortality in ADHF patients with and without DM. Additionally, heatmaps visualized the association between CTI components and mortality: to summarize, the mortality risk is relatively low when the triglyceride-glucose index remains within specific ranges (8.25-9.0 for patients with DM; 7.0-9.0 for non-DM patients) and the C-reactive protein level is maintained below 50 mg/L. Further subgroup analyses highlighted distinct risk modulation patterns: non-DM ADHF patients exhibited mortality risk heterogeneity across gender, hypertension, and stroke subgroups; however, the DM comorbid group demonstrated uniform risk profiles with no statistically significant differences.DiscussionThis study demonstrates the clinical utility of the novel inflammatory-metabolic index CTI in mortality risk assessment for ADHF patients, with superior risk stratification efficacy observed in those with DM comorbidity.